Pengaruh Likuiditas, Profitabilitas dan Ukuran Perusahaan pada Perusahaan Manufaktur di Bursa Efek Indonesia - Septi, Septian Ambriana; Effendi, Syahril (LPPM Universitas Putera Batam, 2021)
Capital is a very important thing for the industry to increase the stability of the industry, without capital the industry cannot grow. So this research aims to identify the effect of liquidity, profitability and company size of the manufacturing industry on the Indonesian stock exchange. This research examines the basic and chemical sub-sector manufacturing industry in 2017-2021. With the number of samples taken 12 companies with purposive sampling method. While the data collection method is the documentation method taken from annual report information. The information analysis method used in this research is the multiple linear regression method. The results of the analysis concluded that liquidity has a significant effect on capital structure, on the other hand, profitability and firm size do not have a significant effect on capital structure.